The Multilateral Aspects of Policies Affecting Capital Flows. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The crisis is prompting a reconsideration of capital flows and the policies that affect them. A breakdown in the domestic stability of a large country can spill over into stress in other countries and even to the global system as a whole. The activities of global institutions and markets-some regulated and some not-can bear on the riskiness of flows. Thus, national policies affecting capital flows can transmit multilaterally. This transmission has not been fully appreciated by national policymakers. Further, they may not have incentives to take full account of the cross-border effects of their policies. Looking ahead, the upward trend in the volume of capital flows can be expected to continue, making it ever more important to address the associated cross-border risks. This paper aims to draw greater attention to the multilateral aspects of policies affecting capital flows. Previous work by the Fund has focused on the policies of recipient countries, mainly emerging market economies (EMEs), and addressed the circumstances in which capital flow management measures (CFMs) would be appropriate. This paper provides a complementary assessment of regulatory and supervisory policies of advanced economies, as well as large advanced economy monetary policy. Moreover, it addresses the multilateral transmission of CFMs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet